P MILITARY ASPECT OF THE ORGANIZATION OF SOCIO-ECONOMIC STRUCTURES IN THE CONDITIONS OF NETWORK COMMUNICATION - Nosach, Bohdan (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2023)
Introduction. The impact of globalization processes in all spheres of society changes the conditions and specifics of modern military conflicts. The aim and tasks are the studies of the specifics of the military aspect of socio-economic structures in the context of network communication as a basis for collective interaction in order to prevent the escalation of armed conflicts and achieve a global security consensus in the modern world. Research methods include functional-instrumental analysis, method of causal analysis in order to further determine the basic quantitative and qualitative and political-legal characteristics of modern military conflicts, system-logical method, method of strategic guidelines, and social modeling to predict the effectiveness of change. Research results. The modern high-tech revolution defines knowledge in various forms as the basis of military strength: the concentration of enemy forces is analyzed by computers, the rules of procedure are determined by programs based on artificial intelligence, and military logistics are carried out in the form of spreadsheets, etc. than automatic weapons. Discussion. According to S. Huntington, in the XX c. the relationship between civilizations has moved from a phase characterized by the only directed influence of one civilization on all others to the stage of intensive, continuous, and multi-vector relationships between all civilizations. Can we say that the period of formation of the holy civilization system of relations is beginning? Conclusion. Two integrated approaches to understanding the military impact on the organization of socio-economic structures in the context of network communication were formed, first, the process of gaining military power as a historical and socio-economic factor in the formation of nation states of Western Europe to study origins, character and boundaries of the modern world management system; secondly, we can say that the forms of military activity, for the most part, are subject to the rules of the market economy of a globalized society. It is proved that the defense sphere directly uses similar intellectual achievements of the civilian economy, therefore the formation of military personnel as "intellectual warriors" today becomes an urgent task. The modern world has a socio-systemic nature of network communication, and society clearly understands the limited nature of its natural resources for which you can fight, but not desirable to destroy. This cardinal contradiction can be resolved only in such sociocultural contexts as science, education, art, etc., which will help change the global tragedy of the destruction of the living space of an individual.